Disseminated cutaneous cysticercosis and neurocysticercosis: A rare occurrence - Sacchidanand, S. (Medknow Publications & Media Pvt Ltd, 2012)
Disseminated cysticercosis is a parasitic infestation of pork tapeworm, Taenia solium. A 19-year-old female presented with multiple nodules all over her body since 12 months. Histopathology showed features suggestive of parasitic granuloma with multinucleated giant cells and plenty of eosinophils admixed with necrosis. Ultrasonography of these lesions showed multiple well-defined cystic lesions of varying size with a few specks of calcification. Cranial computed tomography scan showed bilateral, multiple, small hyperdense lesions in the supratentorial compartment. She was treated with oral albendazole and oral corticosteroids. This case is being reported because of its rare, disseminated nature with cutaneous, neural and ocular involvement.